Efek Strategi Komunikasi Pemasaran Personal Selling PT Agricon Pada Petani Padi di Kabupaten Karawang - Nindya Ayu Wradsari; Anna Fatchiya (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2014)
The objective of this research was to determine the personal selling of marketing communication strategy which was conducted by PT Agricon and to examine the factors related to the effects of it. This research applies simple random sampling which was conducted by using quantitative methods and supported by qualitative approach. The result showed that there were several activities which were implemented by the formulators of personal selling in the Village Rawagempol, such as demo plots, farmers meeting, field trip, and one day promo. Factors that are correlates positively to the tendency of farmer to buy the products are formulator communication skill in attracting farmer attention, the ability to explain the advantages of the product, the ability to use props well, farmer communication skill in being critical to formulator, and the ability of farmer to deliver attention and listen to the formulator. On farmer characteristics side, there were no factors that correlate to the tendency of farmers to buy the products.Keywords: effect communication, marketing communication, personal selling